Surface water and groundwater interaction at long-term exploited riverbank filtration site based on groundwater flow modelling (Mosina-Krajkowo, Poland) - Magdalena Matusiak (Journal of Hydrology: Regional Studies, 2021)
Study region: Poland, Warta River catchment. Study focus: The study aimed to explain the reasons for spatial variability in chloride concentrations at the Mosina-Krajkowo riverbank filtration (RBF) site located along the river. This variability is attributed to RBF’s different intensity along the river sections, related, among others, to clogging development. The RBF effectiveness was studied using groundwater flow modelling by: examining the water balance in zones established on hydrogeological setting and chloride concentrations; travel time of the bankfiltrate investigation; RBF parametrisation (i.e. infiltration per unit area and specific infiltration per unit of riverbank). New Hydrological Insights for the Region: The study identifies zones of the most favourable RBF conditions and establishes the variability causes. The overall share bankfiltrate was found at 75.8 %. Its spatial variation ranged widely from 41.1–89.3%, confirming the usefulness of the RBF performance sectional analysis in managing this type of site. The highest proportion of surface water (>80 %) occurred along the straight river section, where the riverbed was built by fine and medium sands (preventing penetration of organic suspension into the aquifer). In contrast, the lowest values (<42 %) occurred in the meander zone (with the most favourable RBF conditions at the beginning of site operation), where deep erosion reached coarse-grained sediments in the river bottom, followed by the development of clogging processes and a decrease in the RBF efficiency with time.